Pharmacology and pharmacotherapy of antimicrobials - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
The history of medicine has witnessed a remarkable breakthrough with the discovery and development of antimicrobials, a group of essential drugs for the treatment of bacterial, fungal, viral and parasitic infections. From early antibiotics to modern antiviral and antifungal agents, these drugs have played a crucial role in reducing morbidity and mortality associated with infectious diseases. According to Goodman & Gilman (2021), "antimicrobials represent one of the most significant milestones in the history of medicine, radically transforming the treatment of previously fatal infections." Rang et al. (2019) corroborate, emphasizing that "the discovery and clinical use of antimicrobials are testaments to the ability of pharmaceutical science to positively impact global health."